The Impact of the Islamic Education Curricula in Achieving Social Peace Preparatory School in Iraqi Kurdistan as a model - Mikael Rasheed Zibari; Manal Salah Aldeen Azeez (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The purpose of this research is to detect and identify the extent to which the Islamic education curricula affect the realization of the principle of social peace for the preparatory stages in Iraqi Kurdistan. The term "social peace" has become a scientific subject of human and cultural value, which is transmitted by intellectuals, specialists and social workers in their writings and intellectual conferences, so that it is noticeable today that there is no community without a call to demand the social peace for the citizen in a way that there should be satisfaction of the needs of the masses within the framework of social justice that renounces the conflict among the groups of the society and provides the appropriate atmosphere for the society to live in a humanitarian framework in which there is cooperation, sense of security and social peace. These lead to educate students, who are the pillar and the future of the society, principles like loyalty, attachment and belonging to the country. This can be achieved only through a number of factors, including a sense of security, safety, tolerance, justice, equality, cooperation and the realization of the principle of solidarity, partnership, good governance and the existence of free and fair media. The school book is the basic tool for the implementation of curricula in schools whereby each curriculum has a specific role in building the personality of the student. Since the curriculum of Islamic education is the basis for the application of the principle of peace through the education of the generation on the tolerated Islamic principles, which included most of them this principle and called it, and the new version of this stage in education is divided into three stages: tenth, eleventh and twelfth stages, we analyzed the curriculum of each stage separately to see how effective it is in spreading the social scale among all strata of society. After analysis, we presented the results and proposals for each stageIn our study, we have relied on the analytical method (descriptive) for its consistency with the nature of the study since it is the most appropriate curriculum for this purpose.